135k views
8 votes
3a =2b + -6 (solve for a)

User Bobsoap
by
5.2k points

2 Answers

7 votes

Answer:

a = (2b-6)/3

Explanation:

3a = 2b + -6

lets make a the subject of the formula

divide both sides of the equation by 3

3a/3 = a = (2b-6)/3

a = (2b-6)/3

User OliverHennhoefer
by
5.2k points
5 votes

Answer:

shown below

Explanation:

3a = 2b - 6

a = (2b - 6) / 3 or 2b / 3 - 2

User Matt Aldridge
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.